Constructivism in the Processes of Online Education - Vargas López, Carlos (2013)
Constructivism, as a pedagogical theory in which teaching and learning processes are framed, has been the basis for face-to-face educational practice, but is it applicable to teaching and learning online? This question was the starting point for this article. Thus, a literature review about constructivism—its definition, advantages, disadvantages, and applicability in online education was conducted. Even though there is a single definition for constructivism, there are scholars who believe it has no real use for teaching and learning; it is this plurality that gives it wide possibilities of usage in online education.